193k views
1 vote
What is 11 m to the -5 power

1 Answer

1 vote

Answer:

On simplifying 11 m to the -5 , we get:
((1)/(161051 * m^5))

Explanation:

As we know by the law of EXPONENTS:


a ^((-m)) = (1)/(a^m)

Also, by the Power, w e get:
(a)^m = a * a * a ....... m times

Here, using the same we find the value of :
(11m)^((-5)), we get:


(11m)^(( -5)) = (1)/((11m)^5) = (1)/(11m * 11m * 11m * 11m * 11m) = (1)/(161051 * m^5) \\\implies (11m)^(( -5)) = (1)/(161051 * m^5)

Hence, on simplifying 11 m to the -5 , we get:
((1)/(161051 * m^5))

User Hardik Gondalia
by
6.4k points